Halal Marketing In Food And Non Food Product. [The Case Of Nestle And Colgate Palmolive]. - Chanderam., Chandra Segar Rama (Universiti Sains Malaysia, 2009)
The case study was about Nestle Malaysia and Colgate Palmolive Malaysia perspective in Halal marketing in food and non food product. Halal always related to food products and less attention given to non food products. Colgate Palmolive is in non food products business mainly producing personal care products. Nestle become pioneer in implementing Halal practices for all its product range. The focus of the case study is on the importance of Halal practices in non food products. The Halal market is very lucrative and growing market. Consumer perception towards Halal has been change from religious point of view to healthy life style. The case is to understand Colgate Palmolive stands on certifying its toothpaste product range with Halal certification and not all its products. The analysis focus on Colgate Palmolive move to certify only its tooth paste products and not all the product range and the implication towards consumer perception towards Colgate Palmolive. The case study also covers Halal market potential in Malaysia and other Muslim countries. It gives overview of the Halal market and its growth.